БНХАУ-ын цөөнх үндэстний хэлний бодлогын тухай тоймлон өгүүлэх нь (1949-1959) - Э., Уриа (Mongolian Studies, 2023)
China has 55 ethnic minorities, accounting for 8% of China's total population. Some ethnic minorities have several dialects, while others have only one or two dialects. As for scripts, some minorities use two or more, while others have no script at the beginning. For example, Mongols have historically used a number of different scripts, including Uighur-Mongolian, Todo, and Soyombo, etc. While Dai ethnic minority of Yunnan Province of China has also used four different scripts. The People's Republic of China emphasizes the language equality of the nationalities, and has consistently upheld and protected the dialects and scripts of all minorities in its national laws and regulations. The first decade of the founding of the People's Republic of China (1949-1959) was the beginning of the development and implementation of state policies on minority dialects and scripts. In this article, we provide an overview of the laws and regulations formulated and implemented by the Government of the People's Republic of China in 1949-1959 for the protection and development of minority dialects and scripts.